Surface topography in two-dimensional ultrasonic rolling 2024-T3 Al-alloy. (April 2022) - Zhu, Lixin; Zheng, Jianxin; Guo, Yonglei; Deng, Hanlin; Shang, Yingju
Abstract: Two-dimensional ultrasonic rolling (TDUR) is a kind of ultrasonic surface strengthening technology that can improve surface topography to enhance the service performance of parts. The surface topography evolution of the workpiece in TDUR depends on the processing parameters, the geometry, physical and mechanical parameters of the workpiece and the roller. And it also depends on the initial state of the pre-treated workpiece surface and the random vibration during processing. In order to study the process of surface topography formation of TDUR under the influence of various factors, the mechanical analysis of the residual area height of the workpiece after turning was first performed. Then the mathematical models of rolling force and penetration depth were established. Sequentially, the surface topography and surface roughness models were established based on the penetration model, the roller motion trajectory and the test results of random vibration. Finally, 2024-T3 Al-alloy was selected for simulation analysis and experimental verification of the models of the surface topography and the surface roughness. The simulation and experimental results show that TDUR can effectively improve the surface topography of the workpiece and reduce its surface roughness R z by more than 80%. When the initial state of the workpiece surface and the random vibration of the machining process are taken into account, the error of the surface roughness prediction value is significantly reduced, compared with the models without considering both factors. So, the new developed surface topography and the surface roughness models can reflect the actual machining effect more realistically. It was also found that the surface roughness after rolling increased with the increase of initial surface roughness, but its reduction rate did not change with the change of initial surface roughness. This paper investigates the formation process of surface topography in TDUR considering the initial state of the workpiece surface, the influence of random vibration during processing and so on. And this work is important for guiding the pre-treatment process and improving the quality and efficiency of TDUR. Graphical abstract: Simulation topography of 2024-T3 Al-alloy based on the constructed surface topography model in two-dimensional ultrasonic rolling. Unlabelled Image